2021
DOI: 10.17159/2078-5151/2020/v58n2a3131
|View full text |Cite
|
Sign up to set email alerts
|

Use of the OVESCO OTSC® Proctology Clip for closure of fistula-in-ano at Wits Donald Gordon Medical Centre - a single centre experience

Abstract: Background: Definitive closure of fistula-in-ano poses an ongoing surgical challenge. The OVESCO OTSC ® Proctology Clip (proctology clip) purports to offer improved preservation of the anal sphincter whilst at the same time curing the fistula by closure. Methods: A retrospective record review was conducted for patients who received the proctology clip as part of the management of fistula-in-ano in the Colorectal Unit at Wits Donald Gordon Medical Centre (WDGMC). Results: There were 19 cases of fistula-in-ano t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…The healing rates of transsphincteric, suprasphincteric, extrasphincteric, and rectovaginal fistulas were 61%, 74%, 100%, and 20%, respectively [50]. However, other results were more disappointing, with a 47% overall success rate, 66.7% for simple, and 38.5% for complex [51].…”
Section: Anal Fistulamentioning
confidence: 99%
“…The healing rates of transsphincteric, suprasphincteric, extrasphincteric, and rectovaginal fistulas were 61%, 74%, 100%, and 20%, respectively [50]. However, other results were more disappointing, with a 47% overall success rate, 66.7% for simple, and 38.5% for complex [51].…”
Section: Anal Fistulamentioning
confidence: 99%
“…There are only three studies in which outcomes after treatment with OTSC are reported exclusively for cryptoglandular anal fistula [123,126,130]. The rate of fistula healing ranged from 47% to 90% and included patients with various levels of fistula complexity.…”
Section: Effects On Fistula Healing Recurrence and Incontinence Follo...mentioning
confidence: 99%
“…As discussed earlier, due to complete involvement of EAS, the most commonly performed procedure, fistulotomy, is contraindicated in these fistulas[ 25 ] unless it is coupled with primary sphincter repair. The newer sphincter-sparing procedures, like video-assisted anal fistula treatment[ 24 ], fistula laser closure[ 24 ], over-the scope clip (OTSC)[ 37 - 39 ], anal fistula plug (AFP)[ 40 ], stem cells[ 28 ] etc, have dismal success rates in complex fistulas. In fact, there are hardly any studies that have analyzed the success rates of these newer procedures in high-5 fistulas.…”
Section: Management Guidelinesmentioning
confidence: 99%